Regulation of integrin and growth factor signaling in biomaterials for osteodifferentiation - Wei, Qiang; Pohl, Theresa Lucie Maria; Seckinger, Anja; Spatz, Joachim P.; Cavalcanti-Adam, Elisabetta A. (Beilstein journal of organic chemistry, 2015)
Stem cells respond to the microenvironment (niche) they are located in. Under natural conditions, the extracellular matrix (ECM) is the essential component the in stem cell niche, in which both integrin ligands and growth factors are important regulators to directly or indirectly modulate the cell behavior. In this review, we summarize the current knowledge about the potential of integrin ligands and growth factors to induce osteogenic differentiation of stem cells, and discuss the signaling pathways that are initiated by both individual and cooperative parameters. The joint effect of integrin ligands and growth factors is highlighted as the multivalent interactions for bone therapy.,